Direct thrombin inhibitor-bivalirudin improved the hemocompatibility of electrospun polycaprolactone vascular grafts. (1st April 2022) - Sun, Qiqi; Si, Jianghua; Zhao, Lili; Wei, Tingting; Wang, Ting; Li, Feiyi; Li, Yi; Shafiq, Muhammad; Wang, Lili; Liu, Ruihua; Zhi, Dengke; Wang, Kai
Abstract: Synthetic artificial vascular grafts are hampered by their low patency rate in substituting small-caliber arteries (inner diameter <6 mm) because of their poor hemocompatibility. As compared to the heparin, bivalirudin (BV), a direct thrombin inhibitor, is a more reliable anticoagulant. In this study, BV-loaded polycaprolactone (PCL) grafts (PCL-BV) were fabricated by electrospinning. The loading rate of BV was approximately 87%. The PCL-BV grafts achieved the sustained release of BV for up to 30 days in vitro, but mainly released in the first 15 days. Scanning electron microscopy (SEM) and mechanical testing revealed that the BV loading did not affect the structure and mechanical properties of PCL grafts. In vitro coagulation analysis showed that the loading of the BV reduced thrombin activity, prolonged hemocompatibility parameters (activated partial thromboplastin time (APTT), prothrombin time (PT) and thromboplastin time (TT)), reduced blood coagulation, and inhibited the adhesion and activation of fibrinogen (FIB) and platelets. The assessment of vascular grafts in a rabbit arteriovenous (AV)-shunt ex vitro and carotid artery implantation in vivo indicated that BV significantly improved the antithrombogenicity and patency of PCL grafts. Overall, these results suggested that the incorporation of BV into electrospun grafts would be an effective approach to improve the hemocompatibility and patency rate of synthetic vascular grafts. Graphical abstract: Image 1